2022
DOI: 10.3389/fmolb.2022.995853
|View full text |Cite
|
Sign up to set email alerts
|

Sonochemical synthesis of a copper reduced graphene oxide nanocomposite using honey and evaluation of its antibacterial and cytotoxic activities

Abstract: The combination of graphene-based materials and inorganic nanoparticles for the enhancement of the nanomaterial properties is extensively explored nowadays. In the present work, we used a sonochemical method to synthesize a copper/reduced graphene oxide (Cu/RGO) nanocomposite using Australian honey and vitamin C as capping and reducing agents, respectively. The honey-mediated copper/reduced graphene oxide (H/Cu/RGO) nanocomposite was then characterized through UV-visible, XRD, HRTEM, and FTIR analysis. The cop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…The reduction process furthermore offers the possibility of co-reducing metal ions to form metal particles on the rGO surface. This technique was prominently investigated aiming for antibacterial properties of Ag/rGO and Cu/rGO powders [ 51 , 52 ]. By adding Ag + -ions prior to the reduction process, graphene oxide and Ag + -ions are simultaneously reduced to rGO and metallic silver by L-Ascorbic acid (see Figure 5 a Insert).…”
Section: Enhancement Of Graphene Lsp Propertiesmentioning
confidence: 99%
“…The reduction process furthermore offers the possibility of co-reducing metal ions to form metal particles on the rGO surface. This technique was prominently investigated aiming for antibacterial properties of Ag/rGO and Cu/rGO powders [ 51 , 52 ]. By adding Ag + -ions prior to the reduction process, graphene oxide and Ag + -ions are simultaneously reduced to rGO and metallic silver by L-Ascorbic acid (see Figure 5 a Insert).…”
Section: Enhancement Of Graphene Lsp Propertiesmentioning
confidence: 99%
“…Graphene-based nanomaterials are cytotoxic because they damage cell membranes due to their very sharp edges [84]. Besides altering cell morphology, nanocomposites decrease metabolic activity in cells, increase oxidative stress, dam-age mitochondria, and ultimately cause DNA damage [35,36,84,85]. Cu/Glu/rGO shows the synergistic effect of copper, glucose, and reduced graphene oxide.…”
Section: Anticancer Activity 421 Cell Viability Testmentioning
confidence: 99%
“…After antibacterial properties, graphene-based copper/copper oxide nanomaterials have also been studied for their anticancer properties [26,35]. Ismail et al synthesized copper/reduced GO nanocomposite via sonochemical method using honey, results show that H/Cu/RGO nanocomposite has good antibacterial and cytotoxic activity against cancer colorectal cell line (HCT11), even in low concentrations and concluded that this nanocomposite is suitable for biomedical applications [36]. Kodous et al used the ultrasonication method to produce Cu/RGO nanocomposites that inhibited human breast cancer cells MCF-7 cancer cells [37].…”
Section: Introductionmentioning
confidence: 99%
“…For example, in situ reduction methods have been explored where reduced graphene oxide and copper nanoparticles are simultaneously synthesized in the presence of a reducing agent like ascorbic acid 16,17 or plant extracts. 18,19 Green synthesis of CuO-rGO [20][21][22] offer advantages in terms of simplicity, environmental friendliness, and reduced processing time. Based on our current understanding, the utilization of CuO-rGO composites has demonstrated successful outcomes in many chemical transformations 23,24 however, its application in polymerization reactions remains unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers are now focusing on developing simpler and greener synthesis methods for the copper‐graphene based nanocomposite. For example, in situ reduction methods have been explored where reduced graphene oxide and copper nanoparticles are simultaneously synthesized in the presence of a reducing agent like ascorbic acid 16,17 or plant extracts 18,19 . Green synthesis of CuO‐rGO 20–22 offer advantages in terms of simplicity, environmental friendliness, and reduced processing time.…”
Section: Introductionmentioning
confidence: 99%